Performance based approach of Cellular Steel Beam (CSB) exposed to fire / Fariz Aswan Ahmad Zakwan...[et al.] - Ahmad Zakwan, Fariz Aswan; Renga, Rao Krishnamoorthy; Ibrahim, Azmi; Mohd. Ismail, Abdul Manaff (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2019)
This paper presents a numerical analysis of simply supported cellular steel beam (CSB) at elevated temperatures. Currently, CSB is increasingly used as the main structural element in multi-storey buildings, warehouses and any steel structures. Typical steel beams are mainly used as a dwelling load bearing capacity. CSB is one of the options to replace the former steel beam. Several advantages can be gained when adopting CSB as the main structural element in structures. However, several drawbacks have restricted the structural performance of CSB under applied load, especially under fire exposure. Fire is one of the major catastrophe that may endanger any structural steel member in a steel frame building under certain duration. It is important to reduce the member temperature induce by fire exposure to prolong the time before the CSB failed. Experimental data available in the literature review will be used to validate with numerical simulation in this research.